2016
DOI: 10.1186/s13023-016-0548-2
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of caregivers of children with inherited metabolic diseases: a qualitative study

Abstract: Background: We sought to understand the experiences of parents/caregivers of children with inherited metabolic diseases (IMD) in order to inform strategies for supporting patients and their families. We investigated their experiences regarding the management of disease, its impact on child and family life, and interactions with the health care system. Methods: From four Canadian centres, we conducted semi-structured telephone interviews with parents/caregivers of children with an IMD who were born between 2006… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
72
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(79 citation statements)
references
References 36 publications
7
72
0
Order By: Relevance
“…Specific for diseases usually emerging in childhood (neurofibromatosis type 1, Marfan syndrome) was parental behaviour perceived as overprotective and burden for patients’ parents. This is in line with other qualitative studies on parental experiences with paediatric rare diseases such as osteogenesis imperfecta,11 inherited metabolic diseases12 13 and Zellweger spectrum disorders14 from a caregivers’ perspective. In these studies, parents of affected children reported to experience concern, emotional stress and feelings of uncertainty and being overwhelmed, which stresses the need for support systems for caregivers of patients with paediatric rare diseases.…”
Section: Discussionsupporting
confidence: 88%
“…Specific for diseases usually emerging in childhood (neurofibromatosis type 1, Marfan syndrome) was parental behaviour perceived as overprotective and burden for patients’ parents. This is in line with other qualitative studies on parental experiences with paediatric rare diseases such as osteogenesis imperfecta,11 inherited metabolic diseases12 13 and Zellweger spectrum disorders14 from a caregivers’ perspective. In these studies, parents of affected children reported to experience concern, emotional stress and feelings of uncertainty and being overwhelmed, which stresses the need for support systems for caregivers of patients with paediatric rare diseases.…”
Section: Discussionsupporting
confidence: 88%
“…The rapid review and evidence map will address the following primary research question: “What outcomes are reported in key publications related to children diagnosed with phenylketonuria and medium-chain acyl-CoA dehydrogenase deficiency?” A secondary research question is “Among key publications as described above, what outcome measurement instruments are described or used to collect data for these outcomes?” The review will build on CIMDRN’s previous work, including a scoping review of patient/parent-reported outcomes in chronic paediatric illness [ 66 ] and qualitative studies of patient/family priorities [ 6 , 66 ].…”
Section: Methodsmentioning
confidence: 99%
“…These conditions exemplify the challenges of delivering high-quality care for children with rare chronic diseases [ 3 ]. Healthcare needs are disproportionately high and often complex [ 4 , 5 ], caregiver burden is known to be substantial [ 6 ], and evidence on the effectiveness of care is sparse and challenging to generate [ 7 , 8 ]. With promising new interventions for IMD (including drug, dietary, stem cell, and surgical therapies) rapidly emerging [ 9 ], it is vital that their efficacy be evaluated in explanatory studies within controlled settings and that their effectiveness comparative to current standard treatment be assessed in pragmatic studies within real-world settings [ 8 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Zurynski's group reported that parents perceived the lack of knowledge amongst clinicians to be a leading cause of diagnostic delays, highlighting an interrelation between two emotional stressors. Similarly, interviews conducted with caregivers of children with inherited metabolic conditions [14] identi ed emotional challenges associated with poor coordination of healthcare services and there is anecdotal evidence about the burden of time and energy required to manage numerous appointments across different specialisms [33]. Having symptoms questioned by healthcare professionals, or being mislabelled with a psychological health issue when trying to seek help for physical symptoms, which 80% of our respondents agreed had impacted mental health, have also been previously been reported as triggers of poor mental health in speci c patient populations [11].…”
Section: Factors Affecting Mental Healthmentioning
confidence: 99%
“…Further evidence is available from condition-speci c qualitative studies, which have used approaches such as interviews or narrative analysis to explore the psychosocial impact of certain rare conditions, and have generally indicated impaired emotional/psychological wellbeing for patients and carers. For example, psychological or psychosocial consequences have been reported amongst individuals, and parents/carers, living with undiagnosed or medically unexplained conditions [11,12]; and parents/carers of individuals with inherited metabolic disorders [13,14].…”
Section: Introductionmentioning
confidence: 99%